2009
DOI: 10.1007/s12562-008-0054-0
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of heavy metals in the sediments of Uranouchi Inlet, Kochi prefecture, Japan

Abstract: The present status of contamination by heavy metals, and the impact of cage culture on sediments at the Uranouchi Inlet, Kochi Prefecture, Japan, were investigated from two stations influenced by intensive aquaculture and a control station, during May-July 2006. The moisture content of the sediments at the aquaculture stations was over 65%, and the organic matter was always over 100 mg/g dry wt. In contrast, the highest moisture content and organic matter at the control station was 45.5% and 62.9 mg/g dry wt, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…These findings did not exceed the hazardous levels for aquatic organisms according to [24]. The pollution index of the sediment called the Schaanning Pollution Index and developed by Schaanning MT (1994), can be determined by using Zn and Cu concentration ranges in relation to pH levels [25]. Gokcekaya Reservoir's pH (8.85 and 9.12) was >7.7, and the sediment Zn and Cu concentrations were also <5.…”
Section: Discussionmentioning
confidence: 92%
“…These findings did not exceed the hazardous levels for aquatic organisms according to [24]. The pollution index of the sediment called the Schaanning Pollution Index and developed by Schaanning MT (1994), can be determined by using Zn and Cu concentration ranges in relation to pH levels [25]. Gokcekaya Reservoir's pH (8.85 and 9.12) was >7.7, and the sediment Zn and Cu concentrations were also <5.…”
Section: Discussionmentioning
confidence: 92%
“…Other studies reported that elevated concentrations of elements such as Cu, Zn, Fe, and Cd in superficial layers of marine sediments are caused by fish farming and decreased as a result of increasing distance from fish cages. Many other studies indicate that this state was mainly attributed to fish food inputs (Chou et al, 2002;Sutherland et al, 2007;Uotila, 1991;Belias et al, 2003;Kempf et al, 2002;Brooks & Mahnken 2003;Smith et al, 2005;Dean et al, 2007;Jaysankar et al, 2009;Rooney & Podemski, 2010;Russell et al, 2011).…”
Section: Figurementioning
confidence: 97%
“…However, high values of Cd, Mn, Pb, Zn and Fe can be related to other important anthropogenic input such as atmospheric emission, fly ash, domestic and industrial effluent discharge and, extensive use of antifouling paints by shipping activities (Sarkar et al, 2004). Many others authors demonstrated that the differences found between control stations and fish farms stations may be attributed to differences in natural background levels as well as, in the case of impacted stations, to differences of element input through fish farm wastes (fish feed and faces) (Brooks & Mahnken, 2003;Dean et al, 2007;Jaysankar et al, 2009). The surface sediment composition under and in the vicinity of the cages is continuously changing depending on the composition of the solids contained in aquaculture effluents (Mendiguchia et al, 2006).…”
Section: Figurementioning
confidence: 99%
“…Uranouchi Inlet, Japan is a semi-enclosed eutrophic inlet with high biodiversity, from unicellular organisms to large animals (Fig. S1) 58,59 . A previous study 16 identified year-round recovery of the Imitervirales community based on amplicon sequence variants of a single marker gene, DNApolB, in Uranouchi Inlet.…”
Section: Density Of Pairsmentioning
confidence: 99%